Psychological targets in elite athletes' rehabilitation - S. E. Nazaryan; N. Z. Orlova; V. I. Pustovoit (National Electronic Information Consortium (NEICON), 2023)
Inability to participate in competitions due to injury is a temporary disability of an athlete, which can be the reason for the exacerbation of stress and neurosis. The article summarizes the ten-year experience of a psychologist in the rehabilitation of athletes. For the first time the factors of the directed psychological support in sports rehabilitation are formulated, the purpose of psychological support of rehabilitation of the athlete - psychological readiness for continuation of sports career is formed. The "targets" of corrective work for the sports medicine psychologist at the stage of rehabilitation of the athlete after trauma are singled out and defined.